2020
DOI: 10.1007/s00134-019-05906-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of severe respiratory infections in immunocompromised patients

Abstract: An increasing number of critically ill patients are immunocompromised. Acute hypoxemic respiratory failure (ARF), chiefly due to pulmonary infection, is the leading reason for ICU admission. Identifying the cause of ARF increases the chances of survival, but may be extremely challenging, as the underlying disease, treatments, and infection combine to create complex clinical pictures. In addition, there may be more than one infectious agent, and the pulmonary manifestations may be related to both infectious and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
159
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(170 citation statements)
references
References 117 publications
4
159
0
7
Order By: Relevance
“…However, little attention was paid to the bacterial and fungal coinfection of this disease, and the standardized testing process of coinfection is still unavailable. It is difficult to distinguish bacterial or fungal infections from existing viral pneumonia based on clinical and radiological performance (Azoulay et al 2020 ). In addition, there are articles indicating that calcitonin may also be an auxiliary means for detecting whether there is bacterial or fungal coinfection (Wiegers et al 2019 ) as the concentration of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and IL-6 increases, which results in the massive production and release of parathyroid-derived calcitonin during bacterial infection.…”
Section: Bacterial and Fungal Coinfection With Sars-cov-2mentioning
confidence: 99%
“…However, little attention was paid to the bacterial and fungal coinfection of this disease, and the standardized testing process of coinfection is still unavailable. It is difficult to distinguish bacterial or fungal infections from existing viral pneumonia based on clinical and radiological performance (Azoulay et al 2020 ). In addition, there are articles indicating that calcitonin may also be an auxiliary means for detecting whether there is bacterial or fungal coinfection (Wiegers et al 2019 ) as the concentration of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, and IL-6 increases, which results in the massive production and release of parathyroid-derived calcitonin during bacterial infection.…”
Section: Bacterial and Fungal Coinfection With Sars-cov-2mentioning
confidence: 99%
“…Although limited by a highly selected (e.g., exclusion of stem cell transplant subjects) and relatively small number of neutropenic patients as well as by consideration of center-dependent outcomes (ventilator-free and ICU-free days), our findings are important. We show that the prognosis of these patients has improved over time even in prospective randomized controlled studies, whereas this trend has previously been observed only in retrospective observational studies [1,6].…”
mentioning
confidence: 48%
“…Vor allem bei blutungsgefährdeten Patienten könnte die Kryobiopsie eine zukünftige Option darstellen [18,21]. Ein rezenter Review des Nine-i-Netzwerks liefert weitere Ausführungen zum differenzierten diagnostischen Vorgehen bei schweren respiratorischen Infekten des immunsupprimierten Patienten [29].…”
Section: Erweiterte Diagnostische Maßnahmenunclassified